Natural disasters in Jammu and Kashmir - Hussain, Sarfraz; Sharma, Geetu (Innovative Research Thoughts, 2017)
India has traditionally been a disaster-prone nation, with various states affected by different kinds of catastrophes. The effect of these catastrophes is increased when a region is prone to several kinds of disasters. “This study attempts to understand the impact of natural and man-made disasters on the people of Jammu and Kashmir (J&K) and Ladakh region in India as well as it also examines the resilience mechanisms adopted by the people, and identifies measures taken by the government in response to these disasters. To understand these disasters’ dynamics, we performed both offline and online desk reviews for this research. The study indicates that J&K and Ladakh area is plagued not only by numerous natural catastrophes like as floods, earthquakes, avalanches, and landslides but also by the terrorism and violence, which has caused unprecedented death and damage. These natural and man-made catastrophes have negatively impacted most areas of life and development in the region. To minimise the hazards, effective disaster risk reduction and management systems, early warning systems and infrastructure need to be improved. In addition, community involvement has to be increased with the aim of resolving the complaints of the people and involving them in the design and execution of sustainable development initiatives.